1994
DOI: 10.1016/0308-8146(94)90131-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein denaturation in frozen stored hake (Merluccius merluccius L.) muscle: The role of formaldehyde

Abstract: Protein solubility of whole and minced muscle of hake (Merluccius merluccius L.) was evaluated at different temperatures of storage:-5°,-12° and-20°C. Proteins soluble in 1% NaCl did not show any change at any of the temperatures of storage, while the 5% NaCl-soluble proteins decreased significantly when whole hake was stored at-5° and-12°C (p < 0.01). A correlation was found between the decrease of solubility and the production of formaldehyde at-5° and-12°C (p < 0.001 and p < 0.01, respectively). Bound forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…There was an increase in the concentration of HCHO throughout storage, and the trend was similar in the salmon fed the three diets. Sotelo et al (1994) found a concentration of 7.5 mg/kg of HCHO in whole hake stored at −20 • C for 155 d. Fajardo (2002) found a HCHO content of 0.09 mg/mL (1.8 mg/kg) and 0.07 mg/mL (1.4 mg/kg) in dogfish Mustelus mentus and cock fish Callorhynchus callorhynchus, respectively, during the fourth month of frozen storage at −18 • C (both species are nongadoids). The coho salmon from this study showed an intermediate HCHO content between those from the two studies cited previously.…”
Section: Dimethylamine and Formaldehyde Contentmentioning
confidence: 97%
“…There was an increase in the concentration of HCHO throughout storage, and the trend was similar in the salmon fed the three diets. Sotelo et al (1994) found a concentration of 7.5 mg/kg of HCHO in whole hake stored at −20 • C for 155 d. Fajardo (2002) found a HCHO content of 0.09 mg/mL (1.8 mg/kg) and 0.07 mg/mL (1.4 mg/kg) in dogfish Mustelus mentus and cock fish Callorhynchus callorhynchus, respectively, during the fourth month of frozen storage at −18 • C (both species are nongadoids). The coho salmon from this study showed an intermediate HCHO content between those from the two studies cited previously.…”
Section: Dimethylamine and Formaldehyde Contentmentioning
confidence: 97%
“…Textural changes are the result of denaturation of proteins, particularly those in the myofibrillar fraction. For these reasons, different methods of measuring protein denaturation have been used to follow textural denaturation (Hultmann and Rustad 2002;Shenouda 1980;Sotelo et al 1994). Among them, protein solubility is the most often chosen, because of its simplicity and relatively good correlations with textural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that formaldehyde produced in certain fish species by the action of trimethylamine oxide demethylase (TMAOase) on TMAO forms cross‐links with proteins,15 resulting in aggregation and toughening of fish muscle 16. This hypothesis is based mainly on studies which have shown a correlation between increase in formaldehyde level and deterioration of texture in cod and hake or using model systems to study the nature of protein–formaldehyde interaction 17. 18 Indeed, in model systems using added formaldehyde, protein aggregation is enhanced, as formaldehyde can produce cross‐links via methylene bridges between positively charged amino acids.…”
Section: Introductionmentioning
confidence: 99%